2004
DOI: 10.1128/aem.70.6.3664-3672.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Identification of Bacterial Contaminants in Semifinal Gelatin Extracts

Abstract: Bacterial contamination of gelatin is of great concern. Indeed, this animal colloid has many industrial applications, mainly in food and pharmaceutical products. In a previous study (E. De Clerck and P. De Vos, Syst. Appl. Microbiol. 25:611-618), contamination of a gelatin production process with a variety of grampositive and gram-negative bacteria was demonstrated. In this study, bacterial contamination of semifinal gelatin extracts from several production plants was examined. Since these extracts are subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 32 publications
2
78
0
3
Order By: Relevance
“…In addition to confirming FAME identifications, ARDRA enabled nine additional identifications at the species level. ARDRA clusters 4,6,7,8,24,28,29, and 30 and strain R-6443 were identified as Bacillus smithii, B. circulans, Bacillus oleronius, B. sporothermodurans, Brevibacillus brevis, Aneurinibacillus aneurinilyticus, Aneurinibacillus thermoaerophilus, Virgibacillus proomii and Paenibacillus thiaminolyticus, respectively ( Table 4). The strains in ARDRA clusters 6, 7, 8, 12, 13, and 24 grouped together with the type strain of the respective species analyzed simultaneously in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to confirming FAME identifications, ARDRA enabled nine additional identifications at the species level. ARDRA clusters 4,6,7,8,24,28,29, and 30 and strain R-6443 were identified as Bacillus smithii, B. circulans, Bacillus oleronius, B. sporothermodurans, Brevibacillus brevis, Aneurinibacillus aneurinilyticus, Aneurinibacillus thermoaerophilus, Virgibacillus proomii and Paenibacillus thiaminolyticus, respectively ( Table 4). The strains in ARDRA clusters 6, 7, 8, 12, 13, and 24 grouped together with the type strain of the respective species analyzed simultaneously in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16,6,8, and 36 isolates of raw milk, the milking equipment, green crop, and fodder, respectively, could not be analyzed since they failed to grow according to the prescribed growth conditions for FAME analysis. These isolates were not further considered.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR-reactions were performed with the following universal primers: 16S rRNA (8bF, 5'-ACTGGGATCCACAGGAGTGCAAACGACG A-3'; 518f, 5'-CCAGCAGCCGCGGTAAT-3'; 1406r, 5'-ACGGGCGGTGTGTRC-3'; and 1512r, 5'-CTGAAGCTTACGGYTAGCTTGTTACGAC TT-3'), gyrA (gyrA-f, 5'-CAGTCAGGAAATGC GTACGTCCTT-3' and gyrA-r, 5'-CAAGGTAA TGCTCCAGGCATTGCT-3'), and rpoB (rpoB-f, 5'-AGGTCAACTAGTTCAGTATGGAC-3' and rpoB-r, 5'-AAGAACCGTAACCGGCAACTT-3') (De Clerck et al, 2004). Each 50 µL PCR reaction mix contained 5 µL Taq buffer 10x, 3 µL MgCl 2 25 mM, 0.4 µL dNTPs 25 mM, 0.5 µL Taqpolymerase 5 U/mL (all reagents from Fermentas), 1.25 µL primer 20 mM, 50 ng genomic DNA and 36.1 µL H 2 O milli-Q.…”
Section: Amplification Of 16s Rrna Rpob and Gyra Genesmentioning
confidence: 99%
“…Many misclassifications have been found in the phylum Firmicutes (Wang et al, 2007). De Clerck et al (2004) reported that the analysis of only the 16S rRNA gene was unsuitable for the species or sub-species identification of the genus Bacillus, particularly of the cereus and subtilis groups. Sequencing of other genes, such as gyrA and rpoB, was suggested to aid in molecular identification of the subtilis group because of the great homology among 16S rRNA sequences (Chun andBae, 2000, Earl et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…is known as a protease producing strain and suppresses the fungal pathogen in soil. 22,23) Moreover, the genus Brevibacillus is not listed as an infectious or toxin-producing microorganism. 24) Phytohormones, which contribute to plant growth and/or plant physiology, have been studied extensively.…”
Section: Discussionmentioning
confidence: 99%